LEVEL OF UNDERSTANDING TOWARDS MENTAL HEALTH ISSUE - Mat Nasir, Nur Qhairunnisa Amalin; Ridzuan, Abdul Rauf; Zainudin, Dini Insyirah; Muazam Shah, Nuralea Adlin; Ab Rahman, Zaizul; Luthfia, Amia; Rudy, Serafiena (I-iECONS e-proceedings, 2023)
In the current era, mental health issues have become common in society. There are several mental health issues commonly known such as sleep disorders, post-traumatic stress disorder, obsessive compulsive disorder, depression, general anxiety disorder and panic disorder. However, the perception and acceptance of mental health by society is closely related based on the individual's level of understanding and knowledge about this issue. Referring to the Ministry of Health (MOH), Health Minister Dr.Zaliha Mustafa, in 2022 there is an increase on the issue regarding mental problems among children, teenagers and adults compared to 2020. Among the problems that were reported are suicidal thoughts, suicide plans, depression, anxiety and stress. The purpose of this study is to determine the level of understanding of mental health issues in the community and to determine the level of negative perception towards people with mental health issues. This study was conducted using quantitative methods through the distribution of Google Form on 338 volunteering respondents. The end results of the study show that the level of understanding regarding mental health issues is high (M=3.38) meanwhile the level of negative perception towards people with mental health issues is a low (M=1.94).